Attractiveness of container shipping as an investment asset class - perspective from an equity investor with investment horizon of 5 years - Koh, Alvin Jia Hao (Nanyang Technological University, 2022)
This paper evaluates the freight market prospects for the container shipping business between 2023 and 2027 from the viewpoint of an investor in the shipping industry. Consequently, this research provides insight into whether investors should consider investing in this area. This research aims to determine if it is viable to participate in the container shipping business based on historical trends and a macroeconomic analysis of the marine industry. First, the demand and supply variables that influence the shipping industry will be analysed to assess the impact on freight rates. Freight rates are excellent predictors of the container shipping market; thus, a projection of freight rates during the investment horizon would offer a strong indication of whether to engage in this venture. After analysing the interactions between the demand and supply components, it has been determined that the overall factors are unfavourable, as the freight rate is anticipated to decline owing to oversupply and demand stabilisation post-Covid. Based on freight rate alone, this volume concludes that the container market is not an attractive investment area at the present time. To determine the total investment viability, we must examine volume 3, which evaluates the container shipping industry using several asset utilisation scenarios.